Optimizing Instant Herbal Drink Production with IoT-Based Sachet Forming Machines to Increase Productivity and Quality - Mohamad Rodhi Faiz; Hasan Ismail; Budi Wibowotomo; Sujito Sujito; Ryan Kurniawan; Moh Zainul Falah; Aya Shofia Mufti (Bulletin of Community Engagement, 2023)
MSMEs Syarimpon and Melos (Melati Losari) are Micro, Small and Medium Enterprises that focus on the production of herbal drinks in Malang Regency. However, during its development, these MSME players experienced several problems, one of which was the packaging process which was carried out manually. This makes the production process take longer and reduces work efficiency. Apart from that, the process of cutting packaging manually also causes a decrease in the quality of the packaging and its contents. To overcome this problem, one solution is to use a counter machine with an automatic counter. By using this machine, MSMEs can speed up the packaging process, produce precise and neat packaging, and provide the freedom to innovate in determining the size of the packaging to be produced. In the process of using this IoT-based Sachet Forming Machine, it has succeeded in increasing the productivity and quality of the packaging process by taking 3 -5 seconds for one herbal drink sachet so that each day it can increase production to 900 sachets per day. Where the packaging process is still done manually so it takes 4-5 minutes so the packaging process per day is only 50 to 100 PCS of herbal drinks. Keywords: Sachet Forming Machine, IoT, MSMEs Syarimpon and Melos